Answer:
The given expression is equal to 25.
Explanation:
The given expression is
![(\frac{125^(2) }{125^{(4)/(3) } } )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/gq4ipl925ftpcwxvb1iib8jg9l52idielw.png)
To simplify this expression, we have to divide powers, which implies to subtract exponenets, as follows
![(\frac{125^(2) }{125^{(4)/(3) } } )=125^{2-(4)/(3) }=125^{(6-4)/(3) }=125^{(2)/(3) }](https://img.qammunity.org/2021/formulas/mathematics/middle-school/csqtou7jjrfi402hvhyc6vmlwf2avnr402.png)
Then, we use the exponent property to transform the obtained power to a root
![125^{(2)/(3) }=\sqrt[3]{125^(2) } =\sqrt[3]{15625} =25](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mrov09u0y5gaj39p6ztly2dcpvqvzwpuxr.png)
Therefore, the given expression is equal to 25.